1993
DOI: 10.1002/eji.1830230531
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes bearing the γδ T cell receptor in acute Brucella melitensis infection

Abstract: A phenotypical analysis carried out by indirect immunofluorescence and two-color cytofluorometry showed that the number of lymphocytes bearing the gamma delta T cell receptor (TcR) heterodimer was dramatically increased in the blood of six children with Brucella melitensis infection. Most in vivo expanded gamma delta T cells reacted with a monoclonal antibody which identifies V delta 2 gene products and a significant proportion expressed CD25 and HLA-DR activation antigens. In addition, whereas only a few gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 35 publications
4
65
0
1
Order By: Relevance
“…Also, it is reported that bacillus Calmette-Guérin vaccine application can exhibit significantly beneficial effect in controlling the malignancy, in particular the bladder cancers (41,42). Because many microbes are indicated to produce and secrete nonpeptide Ags for human ␥␦ T cells such as alkyl pyrophosphates and alkyl amines (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), it is tempting to speculate that these microbial nonpeptide Ags may contribute to the restriction of growth of incidental tumor cells via stimulation of ␥␦ T cells to proliferate and produce IFN-␥ as well as sensitization of the tumor cells for the ␥␦ T cell-mediated cytotoxicity. Our recent report suggested that ␥␦ T cells might provide innate immunity in patients with renal cell carcinomas, implicating a possible link between tumor immunity and urinary infections (56).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is reported that bacillus Calmette-Guérin vaccine application can exhibit significantly beneficial effect in controlling the malignancy, in particular the bladder cancers (41,42). Because many microbes are indicated to produce and secrete nonpeptide Ags for human ␥␦ T cells such as alkyl pyrophosphates and alkyl amines (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), it is tempting to speculate that these microbial nonpeptide Ags may contribute to the restriction of growth of incidental tumor cells via stimulation of ␥␦ T cells to proliferate and produce IFN-␥ as well as sensitization of the tumor cells for the ␥␦ T cell-mediated cytotoxicity. Our recent report suggested that ␥␦ T cells might provide innate immunity in patients with renal cell carcinomas, implicating a possible link between tumor immunity and urinary infections (56).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained for Macaca mulatta 24,25 and Macaca fascicularis 26 monkeys although we know that monkeys have some cells expressing Vγ2 chains paired with Vδ1 27 (a combination that is infrequent for adult human beings) and that subset will influence the repertoire. The Vγ2-Jγ1.2+ subset responds to a variety of pathogens [28][29][30][31][32][33] and tumor cells [34][35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…Isopentenyl pyrophosphate (IPP), 4 a 246-Da molecule with a five-carbon isoprenyl chain and a pyrophosphate moiety, has been described as the first structurally identified ligand for human ␥␦ T cells (11). Recently, 3-formyl-1-butyl pyrophosphate, a precursor in the synthesis pathway of IPP, was identified as the most likely natural ligand of V␥9V␦2 T cells in parasitic and bacterial infections (12).…”
mentioning
confidence: 99%